Principal Managerial Competence in Improving Teacher Performance at SMP PGII Bandung - Sutarman, Sutarman (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2023)
The research objective is to find out (1). Planning for school principals in improving teacher performance at SMP PGII Bandung (2). Implementation of school principals in improving the performance of school teachers (3). Supervision of school principals in improving teacher performance in schools. The research method used is a qualitative approach. Data collection techniques: through interviews, observation, and document study. Data analysis classifies data, connects data, reduces data, displays data, and draws conclusions. Data validity by testing credibility, transferability, dependability, and confirmability. Findings (1). Planning for school principals to improve teacher performance in schools has carried out long, medium, and short-term planning by involving all stakeholders in preparing school work plans. (2). Implementation of school principals to improve teacher performance has been going according to plan. As in the leadership and motivation that has been carried out. The facilities are sufficient to run optimally. (3). Supervision is carried out by the principal following the supervisory procedures applied to all activities carried out in schools. Assessing program activities that are not implemented according to consideration, because of the assignment, position, and welfare received by the teacher.